Resilient Sustainable Supply Chain Management - A Conceptual Framework - Chowdhury Md. Maruf Hossan; Dewan, Mohammed Naim Ahmed; Quaddus, Mohammed (International Conference on E-Business, 2012)
A resilient-sustainable supply chain has become a unanimously important research agenda in business as global supply chain is facing an increased number of risks and disruptions. In such a situation in order to be competitive and sustainable a supply chain needs to be resilient. Literature related to supply chain sustainability and resilience in an integrated fashion is sparse, rather issues are presented separately and no empirical work has yet been done to develop a resilient-sustainable supply chain management (RSSCM) framework. A resilient-sustainable supply chain management (RSSCM) framework is formulated and measurement scale for resilience and sustainability is developed in this study. The study combines the stakeholder theory and resource based view in line with sustainability and resilience in developing a theoretically grounded, comprehensive framework of resilient-sustainable supply chain management.